Desenvolvimento de interfaces em diferentes tecnologias para teleoperação de robôs móveis. - Luis Felipe Hussin Bento (2010)
Human-Robot Interaction (HRI) is a novel field that is attracting researchers from various areas, such as robotics and human-computer interaction as well as from the field of the humanities including psychology, anthropology and sociology. This growing interest is motivated by the increasing number of robots being used in society (e.g., entertainment, health care and home activities) by people who are not specialists, creating demands on interaction quality. This work proposes the identification of sign classes for the human-robot interaction based on the semiotic engineering, an HCI theory that considers the interaction between people and computers as a particular case of the computer-mediated communication between humans. With the application of an inspection method based on the theory, the Semiotic Inspection Method, the existing interfaces used to control an e-Puck robot, a small robot for academic uses, the sign classes that compose the signification system were identified. Then, a single interaction model was created to represent and evaluate this signification system, resulting in three different interfaces to control the e-Puck: one for desktop PCs, by using the keyboard and mouse; other for tablet PCs, based on the interaction using a pen directly on the screen; and one for a mobile device (an iPod touch R), which allows interaction through its touch screenand the movement of the device itself. The interfaces were evaluated with user participation and the obtained results were promising. They indicated that the signification system is adequate to the interaction with robots, and not only to the kind of tasks and robots mentioned, but also to more complex tasks and other robot types. The work also allowed to identify some limitations and interaction strategies regarding the three interface types evaluated.